A class of α-amino acids-derived multifunctional amidophosphane precatalysts: application to the highly enantio- and diastereoselective silver(I)-catalyzed 1, 3-dipolar cycloaddition reaction. Issue 7 (15th July 2017) - Hou, Yihui; Zhou, Zhipeng; Liu, Pingle; Wang, Jiankang; Hou, Qinglin; Wen, Pushan; Wang, Haifei
Graphical abstract: Abstract: A class of multifunctional amidophosphanes derived from chiral α-amino acids have been developed with two amide bonds, a tertiary amine and a phosphine. In combination with Ag(I) salts, these amidophosphanes have been demonstrated as highly efficient multifunctional catalysts in the asymmetric 1, 3-dipolar cycloaddition of azomethine ylides as well as the three-component reaction of the α-iminoesters in situ generated. Under optimal conditions, highly functionalized endo -8 pyrrolidines were obtained with good to excellent yields (up to 99% yield) and enantioselectivities (up to 98% ee). Abstract : tert -Butyl(( S )-1-((( S )-2-(dimethylamino)-1-phenylethyl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)carbamate: C12 H35 N3 O3 [ α ]D 30 = +18.9 ( c 1.06, CH2 Cl2 ) Absolute configuration: ( S )( S ) Source of chirality: ( S )-phenylglycine and ( S )- tert -leucine Abstract : tert -Butyl(( R )-1-((( S )-2-(dimethylamino)-1-phenylethyl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)carbamate: C12 H35 N3 O3 [ α ]D 30 = +35.2 ( c 0.91, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )- tert -leucine Abstract : tert -Butyl(( R )-1-((( S )-1-(dimethylamino)-3, 3-dimethylbutan-2-yl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)carbamate: C19 H39 N3 O3 [ α ]D 30 = +26.7 ( c 1.20, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )- tert -leucine and ( R )- tert -leucine Abstract : tert -Butyl(( R )-1-((( S )-2-(dimethylamino)-1-phenylethyl)amino)-3-methyl-1-oxobutan-2-yl)carbamate: C20 H33 N3 O3 [ α ]D 30 = +42.3 ( c 1.33, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )-valine Abstract : tert- Butyl (( R )-2-((( S )-2-(dimethylamino)-1-phenylethyl)amino)-2-oxo-1-phenylethyl)carbamate: C23 H31 N3 O3 [ α ]D 30 = −39.1 ( c 0.82, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )-phenylglycine Abstract : tert- Butyl (( S )-2-((( S )-2-(dimethylamino)-1-phenylethyl)amino)-2-oxo-1-phenylethyl)carbamate: C23 H31 N3 O3 [ α ]D 30 = +93.4 ( c 1.00, CH2 Cl2 ) Absolute configuration: ( S ) Source of chirality: ( S )-phenylglycine Abstract : ( S )- N -(2-(Dimethylamino)-1-phenylethyl)-2-(diphenylphosphino)benzamide: C29 H29 N2 OP [ α ]D 30 = +7.2 ( c 0.21, CH2 Cl2 ) Absolute configuration: ( S ) Source of chirality: ( S )-phenylglycine Abstract : N -(( S )-1-((( S )-2-(Dimethylamino)-1-phenylethyl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)-2-(diphenylphosphino)benzamide: C35 H40 N3 O2 P [ α ]D 30 = +11.2 ( c 0.60, CH2 Cl2 ) Absolute configuration: ( S )( S ) Source of chirality: ( S )-phenylglycine and ( S )- tert -leucine Abstract : N -(( R )-1-((( S )-2-(Dimethylamino)-1-phenylethyl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)-2-(diphenylphosphino)benzamide: C35 H40 N3 O2 P [ α ]D 30 = +31.7 ( c 0.83, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )- tert -leucine Abstract : N -(( R )-1-((( S )-1-(Dimethylamino)-3, 3-dimethylbutan-2-yl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)-2-(diphenylphosphino)benzamide: C35 H44 N3 O2 P [ α ]D 30 = +10.7 ( c 0.60, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )- tert -leucine and ( R )- tert -leucine Abstract : N -(( R )-1-((( S )-1-(Dimethylamino)-3, 3-dimethylbutan-2-yl)amino)-3, 3-dimethyl-1-oxobutan-2-yl)-2-(diphenylphosphino)benzamide: C34 H38 N3 O2 P [ α ]D 30 = +31.1 ( c 1.00, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )-valine Abstract : N -(( R )-2-((( S )-2-(Dimethylamino)-1-phenylethyl)amino)-2-oxo-1-phenylethyl)-2-(diphenylphosphino)benzamide: C37 H36 N3 O2 P [ α ]D 30 = −58.6 ( c 1.00, CH2 Cl2 ) Absolute configuration: ( R )( S ) Source of chirality: ( S )-phenylglycine and ( R )-phenylglycine Abstract : N -(( S )-2-((( S )-2-(Dimethylamino)-1-phenylethyl)amino)-2-oxo-1-phenylethyl)-2-(diphenylphosphino)benzamide: C37 H36 N3 O2 P [ α ]D 30 = +91.4 ( c 1.20, CH2 Cl2 ) Absolute configuration: ( S )( S ) Source of chirality: ( S )-phenylglycine Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-phenylpyrrolidine-2, 3, 4-tricarboxylate: C18 H23 NO6 [ α ]D 30 = −54.2 ( c 1.02, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 S, 3 R, 4 S, 5 R )-3, 4-Diethyl 2-methyl 5-phenylpyrrolidine-2, 3, 4-tricarboxylate: C18 H23 NO6 [ α ]D 30 = +58.7 ( c 1.30, CH2 Cl2 ) Absolute configuration: (2 S, 3 R, 4 S, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-( p -tolyl)pyrrolidine-2, 3, 4-tricarboxylate: C19 H25 NO6 [ α ]D 30 = −46.6 ( c 1.20, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 S, 3 R, 4 S, 5 R )-3, 4-Diethyl 2-methyl 5-( p -tolyl)pyrrolidine-2, 3, 4-tricarboxylate: C19 H25 NO6 [ α ]D 30 = +43.4 ( c 1.00, CH2 Cl2 ) Absolute configuration: (2 S, 3 R, 4 S, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(4-methoxyphenyl)pyrrolidine-2, 3, 4-tricarboxylate: C19 H25 NO7 [ α ]D 30 = −48.0 ( c 1.30, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 S, 3 R, 4 S, 5 R )-3, 4-Diethyl 2-methyl 5-(4-methoxyphenyl)pyrrolidine-2, 3, 4-tricarboxylate: C19 H25 NO7 [ α ]D 30 = +44.2 ( c 0.93, CH2 Cl2 ) Absolute configuration: (2 S, 3 R, 4 S, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(4-fluorophenyl)pyrrolidine-2, 3, 4-tricarboxylate: C18 H22 FNO6 [ α ]D 30 = −52.8 ( c 1.14, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 S, 3 R, 4 S, 5 R )-3, 4-Diethyl 2-methyl 5-(4-fluorophenyl)pyrrolidine-2, 3, 4-tricarboxylate: C18 H22 FNO6 [ α ]D 30 = +48.6 ( c 1.10, CH2 Cl2 ) Absolute configuration: (2 S, 3 R, 4 S, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(4-chlorophenyl)pyrrolidine-2, 3, 4-tricarboxylate: C17 H24 ClNO6 [ α ]D 30 = −46.2 ( c 0.92, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(naphthalen-2-yl)pyrrolidine-2, 3, 4-tricarboxylate: C22 H25 NO6 [ α ]D 30 = −32.4 ( c 1.10, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(furan-2-yl)pyrrolidine-2, 3, 4-tricarboxylate: C16 H21 NO7 [ α ]D 30 = −36.8 ( c 1.43, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(thiophen-2-yl)pyrrolidine-2, 3, 4-tricarboxylate: C16 H21 NO6 S [ α ]D 30 = −40.2 ( c 1.20, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(pyridin-3-yl)pyrrolidine-2, 3, 4-tricarboxylate: C17 H22 N2 O6 [ α ]D 30 = −48.5 ( c 0.84, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 R )-3, 4-Diethyl 2-methyl 5-cyclohexylpyrrolidine-2, 3, 4-tricarboxylate: C18 H29 NO6 [ α ]D 30 = −4.3 ( c 0.95, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 R )-3, 4-Diethyl 2-methyl 5-neopentylpyrrolidine-2, 3, 4-tricarboxylate: C17 H29 NO6 [ α ]D 30 = ±2.6 ( c 1.00, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 R ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 2-methyl-5-phenylpyrrolidine-2, 3, 4-tricarboxylate: C19 H25 NO6 [ α ]D 30 = −41.2 ( c 1.25, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 2-methyl-5-( p -tolyl)pyrrolidine-2, 3, 4-tricarboxylate: C20 H27 NO6 [ α ]D 30 = −26.9 ( c 0.75, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(4-fluorophenyl)-2-methylpyrrolidine-2, 3, 4-tricarboxylate: C19 H24 FNO6 [ α ]D 30 = −34.6 ( c 1.34, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 5-(4-bromophenyl)-2-methylpyrrolidine-2, 3, 4-tricarboxylate: C19 H24 BrNO6 [ α ]D 30 = −25.6 ( c 1.40, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 2-methyl-5-(naphthalen-2-yl)pyrrolidine-2, 3, 4-tricarboxylate: C23 H27 NO6 [ α ]D 30 = −19.8 ( c 1.06, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-3, 4-Diethyl 2-methyl 2-benzyl-5-phenylpyrrolidine-2, 3, 4-tricarboxylate: C26 H31 NO6 [ α ]D 30 = −34.1 ( c 1.12, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 3 S, 4 R, 5 S )-Trimethyl 5-phenylpyrrolidine-2, 3, 4-tricarboxylate: C16 H19 NO6 [ α ]D 30 = −60.8 ( c 0.84, CH2 Cl2 ) Absolute configuration: (2 R, 3 S, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (2 R, 4 R, 5 S )-Dimethyl 5-phenylpyrrolidine-2, 4-dicarboxylate: C14 H17 NO4 [ α ]D 30 = −27.4 ( c 1.04, CH2 Cl2 ) Absolute configuration: (2 R, 4 R, 5 S ) Source of chirality: Organocatalysis Abstract : (1 R, 3 S, 3a R, 6a S )-Methyl 4, 6-dioxo-3, 5-diphenyloctahydropyrrolo[3, 4- c ]pyrrole-1-carboxylate: C20 H18 N2 O4 [ α ]D 30 = −78.5 ( c 1.34, CH2 Cl2 ) Absolute configuration: (1 R, 3 S, 3a R, 6a S ) Source of chirality: Organocatalysis